2019
DOI: 10.7554/elife.46149
|View full text |Cite
|
Sign up to set email alerts
|

Identification of potential biomarkers of vaccine inflammation in mice

Abstract: Systems vaccinology approaches have been used successfully to define early signatures of the vaccine-induced immune response. However, the possibility that transcriptomics can also identify a correlate or surrogate for vaccine inflammation has not been fully explored. We have compared four licensed vaccines with known safety profiles, as well as three agonists of Toll-like receptors (TLRs) with known inflammatory potential, to elucidate the transcriptomic profile of an acceptable response to vaccination versus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 58 publications
3
24
0
Order By: Relevance
“…This research aimed to associate the transcriptomic changes in peripheral blood with those in sorted cell populations, and to dissect out the local responses underlying differential reactogenicity to different adjuvants. These results are supported by parallel preclinical BIOVACSAFE studies on adjuvants, as done for alum and MF59 in mice 7,10 . The collected data will be subjected to integrated systems biology studies, to identify the biomarkers that could accelerate development of safer and more effective new vaccines.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…This research aimed to associate the transcriptomic changes in peripheral blood with those in sorted cell populations, and to dissect out the local responses underlying differential reactogenicity to different adjuvants. These results are supported by parallel preclinical BIOVACSAFE studies on adjuvants, as done for alum and MF59 in mice 7,10 . The collected data will be subjected to integrated systems biology studies, to identify the biomarkers that could accelerate development of safer and more effective new vaccines.…”
Section: Discussionsupporting
confidence: 56%
“…The objective was to identify putative biomarkers of inflammation or reactogenicity that could guide the design of follow-on large scale non-residential confirmatory studies using selected vaccines and time points. Combined with preclinical studies conducted in parallel 710 , this data-set informed the design of subsequent clinical research phases aiming to confirm or refute the validity of these putative biomarkers. In this work, we applied an integrated systems biology approach based on the analysis of high-throughput data combined with detailed clinical and laboratory parameters 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have demonstrated the safety of vaccination during pregnancy 24,25 . A recently published study 26 from the same consortium (Biovacsafe) using the same analytical approaches observed that the chemokines CXCL10 and CCL2 were associated with vaccine-induced inflammation. We Fig.…”
Section: Discussionmentioning
confidence: 94%
“…Total RNA preparation from tissue samples Small pieces of mouse muscle tissue (3 mm × 3 mm × 3 mm) were harvested and flash frozen in liquid nitrogen 26 . Total RNA isolation (including microRNA (miRNA) species) was performed using the miRNeasy Mini Kit (Qiagen, UK), as described in the standard protocol for purification of miRNA and total RNA from tissues and cells.…”
Section: Ethics Statementmentioning
confidence: 99%
“…Clinical studies of viral infections in humans [ 5 , 8 , 9 ], including COVID-19 [ 10 ], suggest that SAA is a sensitive biomarker for early diagnostics and treatment and a predictor of the viral disease outcome. Mouse model studies report that SAA3 is a sensitive biomarker of excessive inflammation upon vaccination [ 11 ] and of macrophage infiltration of the adipose tissue in obesity [ 12 ]. Whether SAA is not just a marker but also an active participant in disease is intensely investigated, and numerous, sometimes conflicting, functions have been ascribed to this mysterious protein.…”
Section: Introductionmentioning
confidence: 99%